Kinerja Karyawan: Peran Kualitas Sumber Daya Manusia, Lingkungan Kerja, dan Budaya Organisasi - Maria Rosvita Hoar; Ignatius Soni Kurniawan; Jajuk Herawati (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to examine the effect of the quality of human resources, work environment, and organizational culture on employee performance. The sampling technique used a saturated sample, with as many as 50 employees at Kantor Pusat Waroeng Spesial Sambal Yogyakarta. Primary data was taken by using a questionnaire. Data were analyzed using multiple linear regression analysis. The results showed that the quality of human resources, work environment, and organizational culture had a positive and significant effect on employee performance. The implication directs the leadership to maintain or improve the implementation of the antecedent variables of employee performance.